Information Technologies In Education - Murodova Nargiza Sobirovna (Genius Journals, 2024)
This article explores the integration and impact of information technologies (IT) in educational settings. It examines how digital tools such as learning management systems, online resources, and interactive platforms enhance teaching and learning experiences. The authors highlight the advantages of IT, including personalized learning, increased accessibility, and the ability to engage students through multimedia. Additionally, the article discusses challenges such as digital divides, privacy concerns, and the need for teacher training in using technology effectively. The authors conclude that while IT has transformative potential, its success in education depends on thoughtful implementation and continuous support for both educators and learners
Keywords: Digital Learning; E-Learning; Educational Technology